2013
DOI: 10.1371/journal.pone.0071522
|View full text |Cite
|
Sign up to set email alerts
|

Frequency-Risk and Duration-Risk Relationships between Aspirin Use and Gastric Cancer: A Systematic Review and Meta-Analysis

Abstract: BackgroundAlthough previous meta-analyses have suggested an association between aspirin use and risk of gastric cancer, current evidence is inconsistent. Additionally, it remains unclear whether there are frequency-risk and duration-risk relationships and if a threshold of effect exists.MethodsWe identified studies by searching MEDLINE and PUBMED databases and reviewing relevant articles. We derived the summary risk estimates using fixed-effects or random-effects model based on homogeneity analysis. The dose-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
42
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 46 publications
4
42
1
Order By: Relevance
“…However, this study did not observe the presence of a significant association between aspirin and breast, advanced prostate or lung cancer [55]. Another meta analysis showed an overall 29% reduced risk of gastric cancer corresponding to long-term aspirin use (≥4 years) [56]. Thus far, the use of prophylactic aspirin for a minimum of 5 years at doses between 75 and 325 mg appears to have a favorable benefit-harm profile, and might reduce the incidence of cancer by 7% in women and 9% in men (relative reduction dependent on age and sex).…”
Section: Chemopreventioncontrasting
confidence: 69%
“…However, this study did not observe the presence of a significant association between aspirin and breast, advanced prostate or lung cancer [55]. Another meta analysis showed an overall 29% reduced risk of gastric cancer corresponding to long-term aspirin use (≥4 years) [56]. Thus far, the use of prophylactic aspirin for a minimum of 5 years at doses between 75 and 325 mg appears to have a favorable benefit-harm profile, and might reduce the incidence of cancer by 7% in women and 9% in men (relative reduction dependent on age and sex).…”
Section: Chemopreventioncontrasting
confidence: 69%
“…Aspirin reduces the risk for oesophageal and gastric cancer by 30-40%. [166][167][168] To a lesser extent, other types of NSAIDs exert a similarly protective influence. [166][167][168] …”
Section: Role Of Nsaids and Antiplatelet Agentsmentioning
confidence: 99%
“…There is also substantial evidence to suggest that use of aspirin or non-aspirin NSAIDs may protect against upper gastrointestinal cancers, including oesophageal and gastric cancer [158,[169][170][171][172]. Metaanalyses of epidemiological studies have also indicated that NSAID use may protect against breast [158,[173][174][175], lung [158,176,177], endometrial [178], ovarian [179,180] and prostate [158,181,182] cancers, but the reported inverse associations of NSAID use with these cancers are weaker than those demonstrated for gastroenterological cancers.…”
Section: Aspirin and Other Non-steroidal Anti-inflammatory Drugsmentioning
confidence: 99%